La tipificación del delito de incendios forestales y de vegetación en el Código Orgánico Integral Penal, y la falta de una protección eficaz para el medio ambiente - Cevallos Luna, María Alexandra (2016)
The Constitution of the Republic of Ecuador Ecuadorian State imposes the primary duty to protect the natural heritage that exists in the country, and it recognizes the right of people to live in a healthy environment, ecologically balanced and free from contamination such as one of the rights of the good life and as a right of freedom of all citizens, likewise mandates the State to take all measures to prevent and remedy environmental damage. Despite the existence of constitutional standards is a behavior that has a high incidence in our country such as forest fires, which have devastated large amounts of hectares of the country, consuming everything that exists in these areas even causing a breach of the species of wild flora and fauna. In reviewing the rules of the Code Penal Integral Organic related to the sanctions imposed on those responsible for forest fires and vegetation is observed that the penalties are too weak and not sufficient to effectively protect the right of people to live in a healthy environment to study this problem has structured this research paper titled: " THE CHARACTERIZATION OF THE CRIME OF FOREST FIRES AND VEGETATION IN THE ORGANIC INTEGRAL PENAL CODE, AND LACK OF EFFECTIVE PROTECTION FOR THE ENVIRONMENT". The research is supported by a comprehensive theoretical study of conceptual, doctrinal , legal, comparative law, order, and results in a research field process all this information collection confirms the existence of a problem and supports the need to raise a proposal , for which the presentation of the respective reform bill at the end of the work is done